Immunophenotypic expression profile of multiple myeloma cases at a tertiary hospital in Nairobi Kenya - Mengich, Isabella; Rajput, Sheerien; Malkit, Riyat; Moloo, Zahir; Kagotho, Elizabeth; Lalani, El-Nasir; Mwirigi, Anne (Frontiers in Medicine, 2023)
Introduction: Multiple myeloma (MM) is a plasma cell neoplasm that constitutes 10-15% of all hematopoietic neoplasms. Kenya is placed amongst the top five African countries for MM incidence and MM-related mortality. Prior studies have suggested that the aberrant expression of Cyclin D1, CD56, CD117 and Ki-67 on neoplastic plasma cells is useful in disease prognostication. The prevalence and significance of expression of these markers in a cohort of MM cases in Kenya has not been studied previously. Methods: A retrospective cross-sectional study was carried out at the Aga Khan University Hospital, Nairobi. The study population included 83 MM cases with available trephine blocks archived between 1st of January 2009 and 31st of March 2020. Immunohistochemical expression of Cyclin D1, CD56, CD117 and Ki-67 was analyzed and scored. The biomarkers were described using frequencies based on the positive and negative results. Fisher’s exact test was used to determine the association between the immunophenotypic markers and categorical variables. Results: Of the 83 selected cases, expression of Cyclin D1, CD56, CD117 and Ki-67 was identified in 28.9%, 34.9%, 7.2% and 50.6% respectively. Cyclin D1 positivity was significantly associated with hypercalcemia. Absence of CD117 expression was noted to be associated with adverse risk parameters including an IgA isotype or light chain disease, International Staging System (ISS) stage III disease, abnormal baseline serum free light chains (sFLC) and a high plasma cell burden. Conclusion: Cyclin D1 expression was congruent with previously reported studies. The frequency of CD56 and CD117 expression was lower than previously reported. This may be due to differences in disease biology between the study populations. Approximately half of cases were Ki-67 positive. Our data showed limited associations between the expression of studied markers and clinicopathologic variables. However, this could be attributed to the small study sample size. We would recommend further characterization of the disease in a larger prospective study with the inclusion of survival outcomes and cytogenetic studies.